'Folklore' multimediatised : african orality in literature, comic strip and animation film : from independence to now - (:unkn) unknown (My University, 2022)
The present study proposes to reflect on the phenomena of self-representation and/or representation of African culture through the multimediaization of its traditional oral narratives on the one hand, and contemporary texts and media productions on the other. Despite the temporal indication in its title, this thesis is not intended to be chronological in the strict sense of the term. It proceeds rather by an approach which is based on the entry into the scene, in Africa, of the various media forms in which we are interested, namely the book, the comic strip and the animated film as well as their capacity to convey this oral and popular culture. This research work focuses particularly on the rewritings of the epic of Soundiata, the legend of Pokou and the story of Aya de Yopougon. The aim is to analyze the changes that these stories undergo as they are rewritten in the media. The interest in these evolutions aims to bring out the differents configurations that the image of Africa can take on in these rewritings. The study shows how some of these configurations, although claiming to be part of the vast traditional and popular African culture, undergo a certain form of actualization through an increased recourse of the authors to cultural exchanges. Finally, the heterogeneous character of the elements of the corpus places this reflection in a comparative perspective.
Keywords: African Research